Vonoprazan on the Eradication of Helicobacter pylori Infection - Huang, Jiaming; Lin, Ye (Turkish Journal of Gastroenterology, 2022)
Background: This study aimed to investigate the efficacy and safety of vonoprazan in the eradication of Helicobacter pylori (H. pylori). Methods: A total of 120 cases of H. pylori-infected outpatients were selected and randomly divided into the traditional quadruple therapy, vonoprazan triple therapy, and vonoprazan quadruple therapy groups. The traditional quadruple therapy group patients were orally treated with esomeprazole (20 mg) 30 minutes before breakfast and supper, amoxicillin (1000 mg orally) 30 minutes after breakfast and supper, furazolidone (100 mg orally) 30 minutes after breakfast and supper, and bismuth potassium citrate (0.6 g orally) 30 minutes before breakfast and supper. The vonoprazan triple therapy group patients were treated with vonoprazan (20 mg orally) 30 minutes following breakfast and supper, amoxicillin (1000 mg orally) 30 minutes following breakfast and supper, and bismuth potassium citrate (0.6 g orally) 30 minutes before breakfast and supper. The vonoprazan quadruple therapy group patients were treated with vonoprazan (20 mg orally) 30 minutes following breakfast and supper, amoxicillin (1000 mg orally) 30 minutes after breakfast and supper, furazolidone (100 mg orally) 30 minutes after breakfast and supper, and bismuth potassium citrate (0.6 g orally) 30 minutes before breakfast and supper. The 3 groups were treated for 14 days, and adverse reactions, such as vomiting and abdominal distension, were recorded during the treatment period. The 14C urea breath test was used to detect whether H. pylori was successfully eradicated in the patients. Results: The eradication rates of the vonoprazan triple therapy, vonoprazan quadruple therapy, and the traditional quadruple therapy groups were 80%, 95%, and 97.5%, respectively. The eradication rate was higher in the vonoprazan triple therapy and in the vonoprazan quadruple therapy groups compared with that noted in the control group. The adverse reactions were mild in these groups, and the main adverse reactions were nausea, abdominal distension, diarrhea, and constipation. The adverse reaction rate was 25%, 7.5%, and 15%, respectively. This rate was lower in the vonoprazan triple therapy and vonoprazan quadruple therapy groups than that noted in the control group. Conclusion: Both vonoprazan triple therapy and vonoprazan quadruple therapy regimens could increase the eradication rate of H. pylori. Vonoprazan triple therapy exhibited reduced side effects and could be applied in the eradication of H. pylori in the clinic. Cite this article as: Huang J, Lin Y. Vonoprazan on the eradication of Helicobacter pylori infection. Turk J Gastroenterol. 2023;34(3):221-226.